PD-L1 small-molecule modulators: A new hope in epigenetic-based multidrug cancer therapy?. Issue 2 (February 2023) - Zwergel, Clemens; Fioravanti, Rossella; Mai, Antonello
Highlights: Short digest on the latest updates regarding immunotherapy with a focus on PD-L1. Summary of the recent advances in the field of small molecule PD-L1 modulators. Overview of the growing interest in rational therapy combinations of PD-L1 modulators with epidrugs. Abstract : Programmed death-ligand 1 (PD-L1) is an immune checkpoint protein the overexpression of which results in an inhibitory signal that induces T cell exhaustion responsible for immune escape in tumors. Immunotherapy strategies targeting the PD-L1 pathway have achieved remarkable success in treating various types of cancer. More recently, numerous advances in understanding the complex PD-L1 biology have been made, and the first small-molecule inhibitors have been described in the literature. In this review, we highlight the most promising recent advances in understanding the complex regulation mechanisms focusing on small-molecule modulators, which could be used in rational therapy combinations with other epigenetic chemotherapeutic agents.